Intracellular Targeting of Gag Proteins of the Drosophila Telomeric Retrotransposons - Rashkova, S. (American Society for Microbiology, 2003)
Drosophila has two non-long-terminal-repeat (non-LTR) retrotransposons that are unique because they have a defined role in chromosome maintenance. These elements, HeT-A and TART, extend chromosome ends by successive transpositions, producing long arrays of head-to-tail repeat sequences. These arrays appear to be analogous to the arrays produced by telomerase on chromosomes of other organisms. While other non-LTR retrotransposons transpose to many chromosomal sites, HeT-A and TART transpose only to chromosome ends. Although HeT-A and TART belong to different subfamilies of non-LTR retrotransposons, they encode very similar Gag proteins, which suggests that Gag proteins are involved in their unique transposition targeting. We have recently shown that both Gags localize efficiently to nuclei where HeT-A Gag forms structures associated with telomeres. TART Gag does not associate with telomeres unless HeT-A Gag is present, suggesting a symbiotic relationship in which HeT-A Gag provides telomeric targeting. We now report studies to identify amino acid regions responsible for different aspects of the intracellular targeting of these proteins. Green fluorescent protein-tagged deletion derivatives were expressed in cultured Drosophila cells. The intracellular localization of these proteins shows the following. (i) Several regions that direct subcellular localizations or cluster formation are found in both Gags and are located in equivalent regions of the two proteins. (ii) Regions important for telomere association are present only in HeT-A Gag. These are present at several places in the protein, are not redundant, and cannot be complemented in trans. (iii) Regions containing zinc knuckle and major homology region motifs, characteristic of retroviral Gags, are involved in protein-protein interactions of the telomeric Gags, as they are in retroviral Gags.